Contribution of Pelabuhan Perikanan Nusantara for Food Supply of Skipjack in Ambon City - Kaihatu, Petrizia J; Setha, Beni; Matakupan, Hansje (AGRITEKNO: Jurnal Teknologi Pertanian, 2022)
The fishery is a source of food. Ambon City as an area that has an ocean area of ​​52% can rely on the fishery sector as a source of protein food. The level of fish consumption in Ambon City in 2019 was 37.01 kg/capita/year with the most consumed type of fish being the type of tuna/ skipjack/tuna. Pelabuhan Perikanan Nusantara Ambon (PPN) is one of the fish landings centers that contribute to the provision of fish food, including skipjack (Katsuwonus pelamis) in Ambon city. The production of skipjack which landed at the Nusantara Fisheries Port (PPN) Ambon in 2014-2020 fluctuated with an average production of 613.51 tons or 32.03%. The highest production was in 2014 at 1,093.54 tons and the lowest was in 2015 at 161.07 tons. Based on the average production of skipjack tuna (Katsuwonus pelamis), PPN contributes 21.14% to the supply of fish food in Ambon City.